KEBAHAGIAAN LANSIA YANG TINGGAL DI PANTI WREDA - Firli Ariska; Wiwien Dinar Pratisti (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Elderly is the final stage of the human life cycle. Every people wants happiness in his life, especially for the elderly who live in nursing homes. The research aims to describe how is the happiness of the elderly who live in nursing homes. The research uses qualitative with a case study approach. This study results showed that all subjects are happy to stay at nursing home and all subjects interpret happiness as feeling happy and satisfied. This is because the subjects can do the activities she likes whether it is related to religious activities or other personal activities, all needs including subjects health are guarenteed, subjects have many friends and subjects has positive hopes for her future.